THE INFLUENCE OF TRUST ISSUES ON INTERPERSONAL RELATIONSHIPS OF UIN CYBER, SYEKH NURJATI CIREBON STUDENTS - ibnu Setiawan Pratama (Jurnal EMPATI, 2026)
Interpersonal relationships are an important factor that affects the quality of life of students. However, in building Interpersonal relationships, Trust Issues are often an obstacle for students to connect and trust others around them. This study aims to analyze: 1) The level of Trust Issues On Interpersonal  At the same time, Shaykh Nurjati Cirebon students were in attendance. 2) Factors that cause Trust Issues in students. 3) The impact of Trust Issues that occur on students. 4) Strategies and efforts in dealing with Trust Issues to students. This research uses a descriptive qualitative method. The data collection techniques applied in this study were interviews and questionnaire distribution. Through interview techniques with 7 students and the distribution of questionnaires to 42 respondents, it was found that 1) The level of Trust Issues in interpersonal relationships experienced as many as 40% of students have a low level of Trust Issues  . 2) Factors that cause Trust Issues include bad experiences in the past, low emotional capacity, poor communication. 3) The impact that occurs due to Trust isssue in students including, feelings of overthinking, strained relationships, feeling lonely. 4) Strategies to deal with Trust Issues About Interpersonal  relationships in students include honest communication, This can help build good relationships with others, accept risks, students are able to accept risks that occur in friendships and get to know new people, such as spending time to get to know others more deeply.